PENGEMBANGAN BUKU SISWA KEANEKARAGAMAN HAYATI BERORIENTASI PROBLEM-BASED LEARNING TERINTEGRASI KEARIFAN LOKAL DAN BERBANTUAN AUGMENTED REALITY UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS SISWA - Thenu, Elsa Cahyunisa; Iwan, Iwan; Jeni, Jeni (FKIP Universitas Tanjungpura, 2025)
Scientific and technological developments have impacted the evolution of education globally, particularly in Indonesia. Students truly need technology-integrated instructional materials in the 21st century learning process so they may master the content through real-world examples and applications. The purpose of this development study is to evaluate the efficacy, usefulness, and validity of the student book that was created. Twenty students served as the trial class for the study, which was carried out at YPK Immanuel Manokwari High School. The ADDIE model, which comprises five stages analysis, design, development, implementation, and evaluation the development model that is employed. With an average evaluation by teaching and material experts of 86.88% and student responses as users on very good practicality criteria with an average response of 82.71%, the results demonstrated that the student book met very valid eligibility criteria to be used as teaching material. However, with an average N-gain value of 0.0067, the pupils' critical thinking skills score is still included in the poor interpretation requirement. According to the study's findings, creating student biodiversity books that incorporate local knowledge and problem-based learning with the help of augmented reality can help students strengthen their critical thinking abilities. Keywords: Student Book, Problem Based Learning, Local Wisdom, Critical Thingking Skills